Implementasi Syariah Product Inovation Monitoring Mechanism Sebagai Wujud Pembangunan Hukum Nasional - Nafi’uddin Fauzi Mahfudh (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine the Implementation of Sharia Product Innovation Monitoring Mechanism as a Form of National Legal Development, The type of research used in this study is normative legal research, Legal research is based on methods, systematics, and thoughts that aim to study one or several specific legal phenomena by analyzing them. In addition, an in-depth examination of the facts is also carried out to solve the problem in question, This study can be categorized using a research approach, namely the statute approach, namely looking for laws and regulations regarding or relating to the issue, examining all laws and regulations related to the legal issue being handled, In an effort to find and collect the data needed, this study uses a data collection technique of document studies or library materials. The discussion in this study is the Implementation of Sharia Product Innovation Monitoring Mechanism can provide solutions to product development in Islamic banking which is required to have conformity with community conditions and developments so that Islamic banking products can attract more customers. Moreover, it is supported by regulations that have sharia substance in the National Legal System. Keywords: Sharia Economics, Islamic Banking, Mechanis